F波からわかる運動観察の臨床応用 - 末廣, 健児; 石濱, 崇史; 鈴木, 俊明; 髙崎, 浩壽 (関西理学療法, 2019)
In rehabilitation, movement observation is applied to improve motor functions. We investigated the effects of movement observation by assessing the excitability changes in the spinal anterior horn cells using the F-wave. In healthy subjects, we found that movement observation accompanying target muscle contraction increased the excitability of the spinal anterior horn cells corresponding to the target muscle. This observation suggests that the use of movement observation may be efficacious for patients with reduced excitability and function of the spinal anterior horn cells. In clinical applications of movement observation, it is important to match the patient’s posture with the observation object, and to present movement of the same side as the treated region.